(untitled) (The Pakistan Development Review, 2020)
Creativity is a skill that the labour market in the coming decade will demand (Csikszentmihalyi, 2006). Students in the 21st century need to be educated in a way that they can tackle the challenges of today’s ill-defined lives; to this end, creativity is the epitome resource and an attribute to address individual, social, and global problems. Though discipline and content may differ, creativity is required everywhere (Beghetto, 2010).